Interactive Effects of Light-Sources, Photoperiod and Strain on Blood Physiological Variables of Broilers Grown to Heavy Weight - Olanrewaju , H.A.; Purswell, J.L.; Collier, S.D.; Branton, S.L. (International Journal of Poultry Science, 2020)
Objective: Effects of light sources, photoperiods and strains on blood physiological variables of broilers grown to heavy weights (>3 kg) were investigated in 2 trials. Materials and Methods: The experimental design was a 4×2×2 factorial consisting of 4 light sources [incandescent (ICD, standard), compact fluorescent (CFL), neutral LED (Neutral-LED) and cool poultry specific LED (Cool-PS-LED)], 2 photoperiods (Regular/intermittent [2L:2D] and Short [8L:16D] and 2 strains (A, B). In each trial, 480 (240 males/240 females) 1-d-old chicks of each strain from different commercial hatcheries were equally and randomly distributed into 16 environmental-control rooms (30 males +30 females/room) at 50% RH. Each room was randomly assigned one of 16 treatments from 1-56 days of age. Birds were provided similar diets. Feed and water were provided ad libitum. Venous blood samples were collected on d 14, 28, 42 and 56 of age and analyzed immediately. Results: Light sources had significant (p<0.05) effects on BW, electrolytes, pCO2, angap, T3 and T4 in comparison with birds reared under ICD. Short photoperiod significantly (p<0.05) reduced BW, pH, pO2, SaO2, electrolytes, Osmo and T3, along with significantly (p<0.05) increased pCO2, Hb, Hct and McHc compared with regular intermittent photoperiod. Acid-base regulation during the short photoperiod exposure had not deteriorated despite higher pCO2 that consequently decreased blood pH due to a respiratory acidosis. Also, Strain B had significantly (p<0.05) increased BW, pCO2, HCO3-, McHc, electrolytes, angap, Osmo and T3, along with significantly (p<0.05) reduced pH level, pO2, SaO2, Hb, Hct and T4 in comparison with Strain A. All these changes were within broilers normal acid-base homeostasis ranges. Plasma corticosterone and blood glucose concentrations were not affected by treatments, indicating an absence of physiological stress. Conclusion: The results indicating that the 3 light sources evaluated along with a regular/intermittent photoperiod in commercial poultry facilities would reduce energy costs and optimize production without compromising the welfare of broilers grown to heavy weights.